Reporting Regulatory Environments and Earnings Management: U.S. and Non-U.S. Firms Using U.S. GAAP or IFRS - Evans, Mark E.; Houston, Richard W.; Peters, Michael F.; Pratt, Jamie H. (The Accounting Review, 2015)
ABSTRACT Based on data collected from 616 experienced financial officers who use U.S. GAAP or IFRS and are domiciled in the U.S., Europe, or Asia, we examine how reporting standards (U.S. GAAP versus IFRS) and domicile (U.S. versus non-U.S.) affect earnings management (real versus accrual). U.S. firms using U.S. GAAP rely more heavily on real methods than non-U.S. firms that use either IFRS or U.S. GAAP and U.S. firms using IFRS. U.S. firms using U.S. GAAP operate in an environment that encourages real over accruals methods; specifically, U.S. GAAP facilitates detection of earnings management, and enforcement is more effective in the U.S. Further, the likelihood and amount of earnings management do not differ across conditions, suggesting that firms using less accruals earnings management tend to fully compensate by increasing real methods. So stronger reporting environments do not necessarily reduce total earnings management, but instead encourage substitution of real for accruals methods.